Growth Performance of Rabbits Fed Palm-Press Fibres-Based Diets - HOUNDONOUGBO, M. FRÉDÉRIC; CHRYSOSTOME, CHRISTOPHE ACHILLE A. MAHUSSI; ATTAKPA, S. EUGÈNE; SEZAN, ALPHONSE; DEHOU, B. HYBRIDE (My University, 2012)
An experiment was carried out to define the optimal rate of palm-press fibres in growing rabbits’ diet. In total, 64 weaned rabbits (35 days old) of Beninese breed were divided in 16 groups of 4 rabbits (2 males and 2 females) each. During six weeks, rabbits were fed with 4 complete diets containing 0% (F0, control), 5% (F5), 10% (F10), and 15% (F15) of fibres from a palm oil industry. Results demonstrated that up to 15 of palm-press fibres can be included efficiently in growing rabbits’ diet. The daily feed intake was not significantly affected by the diet (P > 0.05). At 13 weeks old, the average live weights of rabbits were 1788.5 g, 1805.0 g, 1718.5 g, and 1801.3 g in respectively, F0, F5, F10 and F15 groups. No mortality of rabbits was recorded. Compared to F0, the feed conversion ratio and feeding cost decreased in the group of rabbits fed F15 diet. The carcass yield was similar between diets.
Keywords: Palm-Press Fibre; Rabbit; Growth performance